2012
DOI: 10.1097/sla.0b013e318252edf8
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effect of Combinations of Immune Modulating Nutrients on Outcome in Patients Undergoing Major Open Gastrointestinal Surgery

Abstract: IMN is beneficial in reducing postoperative infectious and noninfectious complications and shortening hospital stay in patients undergoing major open gastrointestinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 55 publications
5
118
1
11
Order By: Relevance
“…However, a recent meta-analysis suggested that preoperative only IMN did not improve outcomes when compared to preoperative isonitrogenous ONS. 70 Additional meta-analyses have demonstrated that postoperative IMN reduces infectious complications, 72,[74][75][76][77] including the recent analysis from Ljungqvist et al 72,[74][75][76][77] One meta-analysis of early enteral postoperative IMN also demonstrated a reduction in anastomotic leaks. 78 Limitations of these data include many early IMN studies informing that these meta-analyses were not balanced with an isocaloric, isonitrogenous controls.…”
Section: Role Of Perioperative Imnmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent meta-analysis suggested that preoperative only IMN did not improve outcomes when compared to preoperative isonitrogenous ONS. 70 Additional meta-analyses have demonstrated that postoperative IMN reduces infectious complications, 72,[74][75][76][77] including the recent analysis from Ljungqvist et al 72,[74][75][76][77] One meta-analysis of early enteral postoperative IMN also demonstrated a reduction in anastomotic leaks. 78 Limitations of these data include many early IMN studies informing that these meta-analyses were not balanced with an isocaloric, isonitrogenous controls.…”
Section: Role Of Perioperative Imnmentioning
confidence: 99%
“…63 Evidence suggests that patients undergoing high-risk GI surgery were the most likely to benefit, possibly due to the higher perioperative risk of complication. 72 Due to the large number of small to medium size trials, many conclusions have been drawn from meta-analyses. In their landmark meta-analysis in 2011, Drover et al 73 demonstrated a 40% reduction in perioperative infectious complications with IMN.…”
Section: Role Of Perioperative Imnmentioning
confidence: 99%
“…Although there is an ongoing debate on the subject and opposing data in the literature, perioperative use of immune-modulating enteral products in patients undergoing major abdominal cancer surgery independent of the patient's nutritional status is recommended in the current ESPEN guidelines for enteral nutrition (16,25,26). These immunonutrition products are reimbursed by the state in Turkey and one would expect the use of such formulas for appropriate indications.…”
Section: Discussionmentioning
confidence: 99%
“…При наличии стойкой дисфагии у больных данной группы на первом этапе осуществляют эндоскопическое стентирование, про-ведение зонда либо гастростомию, поскольку на началь-ном этапе облучения дисфагия может нарастать вследствие отека. Своевременное и правильное назначение гиперни-трогенных смесей (смесей с повышенным содержанием белка) для энтерального питания способно остановить процесс потери массы тела, нормализовать питательный статус больных, а также способствовать профилактике осложнений противоопухолевой терапии, в частности ин-фекционных [12,13].…”
Section: показания к лечебному питанию и способы нутритивной поддержкиunclassified